STUDY OF IRRIGATION MODERNIZATION READINESS WITH IKMI AND AHP METHOD (CASE STUDY : SAUSU IRRIGATION AREA CENTRAL SULAWESI) - Manto Waney, Andrew
Assessment the readiness of an Irrigation Area to take part in an irrigation modernization program is carried out using the Irrigation Modernization Readiness Index (IKMI). The measurement of performance by the IKMI method is based on Irrigation Performance Measurement as implemented in the Minister of Public Works and Public Housing Regulation No.12 / PRT / M / 2015 concerning Exploitation and Maintenance Irrigation Network and Minister of Public Works and Public Housing Regulation No.23 / PRT / M / 2015 concerning Management of Irrigation Assets which produces 5 (five) irrigation pillars as the main indicators, namely: water availability, irrigation infrastructure, management systems, management institutions, and human power resources. Furthermore, the weight distribution of the irrigation pillar with the IKMI method was compared with the determination of weights using the AHP (Analitycal Hierarchy Process) method based on stakeholder understanding. AHP analysis is also carried out on the predicate of lower threshold assessment of irrigation modernization readiness. In this study the Irrigation Area that was reviewed at the Sausu Irrigation Area in Parigi Moutong Districts Central Sulawesi Province. From the AHP analysis the results of the weighting of the irrigation pillar were obtained, namely on the water availability pillars by 33,82 %, the irrigation infrastructure pillars by 23,91 %, the management system pillars by 16,47 %, the management institutions pillars by 13,53 %, and the human power resources pillars by 12,26 %, resulting in an irrigation modernization readiness rate of 80,58 %. This figure is different if the weighting is done using the weight and assessment method by the Irrigation and Swamp Directorate of the Ministry of Public Works and Public Housing which is equal to 78,10 %. The predicate of this readiness number is in the category of "sufficient" if the assessment use the IKMI method and the category "adequate" if the assessment use the AHP.